PERANCANGAN SIMULASI DIGITAL VAN DE GRAAFF BERBASIS WEB SEBAGAI MEDIA PRAKTIKUM LISTRIK STATIS - Siti Mu'awanah; Alfriza Sri Ningsih Manik; Erlida Amnie Lubis (JURNAL FIRNAS, 2026)
Abstract: This research aims to develop a digital simulation of the Van de Graaff Generator as an alternative medium for static electricity practicums while also developing a valid and suitable user guide for physics learning in schools. This development is driven by a research gap, namely the limited availability of physical Van de Graaff Generators in schools and the absence of digital simulations that specifically visualize typical phenomena such as hair standing on end or the movement of paper pieces, and the absence of local simulations that allow flexible adjustment of experimental variables according to curriculum needs. The simulation was designed through a virtual physics experiment using HTML, CSS, and JavaScript and then validated by comparing the results of calculations of electric potential, electric field, and Coulomb force at various distances with theory. The results show that the simulation works stably, interactively, and very accurately, with a 98% agreement level, and is able to display patterns of V, E, and F decreases that are consistent with Coulomb's Law, making it suitable as an alternative physical teaching aid in static electricity learning.